Aid allocation and fragile states - Mark McGillivray (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This paper summarises research on aid allocation and effectiveness, highlighting the current findings of recent research on aid allocation to fragile states. Fragile states are defined by the donor community as those with either critically poor policies or poorly performing institutions, or both. The paper examines the research findings in the broader context of research and analysis on how aid should and is being allocated across all developing countries. Various aid allocation models and their implications for aid to fragile states are considered. The paper also looks at types of instruments and their sequencing in fragile states.
Keywords: F35; E61; I31; O19; 330; aid; fragile states; volatility; growth; poverty; MDGs; Entwicklungshilfe; Allokation; Entwicklungsländer